1996
DOI: 10.1002/(sici)1099-1646(199603)12:2/3<273::aid-rrr395>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Method for Modelling Spawning Habitat Dynamics of Landlocked Salmon,salmo Salar

Abstract: The stability of habitat conditions determined by the hydrological regime of a river can play a major part in fish spawning success. Application of the classical IFIM approach (Instream Flow Incremental Methodology) does not usually take into account this dynamic aspect of the habitat. We developed a numerical method to simulate the rate of variation in spawning habitat conditions using two‐dimensional hydrodynamic modelling coupled with a fish model based on habitat suitability indices (HSI). The approach ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…However, consistent with our previous studies, the errors of commission (predicted to be a spawning site but not used) were high at some sites (see Task c for comments on results). At these sites, we plan to conduct a more detailed analysis using ideas that are based in part on the reasoning developed in Leclerc et al (1996). Specifically, we will test whether there are differences in the stability of habitat between cells that are predicted to be habitat and are used versus areas that are predicted to be habitat but are not used.…”
Section: Task a Conduct Limits Analysismentioning
confidence: 99%
“…However, consistent with our previous studies, the errors of commission (predicted to be a spawning site but not used) were high at some sites (see Task c for comments on results). At these sites, we plan to conduct a more detailed analysis using ideas that are based in part on the reasoning developed in Leclerc et al (1996). Specifically, we will test whether there are differences in the stability of habitat between cells that are predicted to be habitat and are used versus areas that are predicted to be habitat but are not used.…”
Section: Task a Conduct Limits Analysismentioning
confidence: 99%
“…Third, it is clear that the threedimensional flow structure of rivers, especially gravel bed rivers exerts a crucial control upon habitat, and its spatial variation. Leclerc et al [1995Leclerc et al [ , 1996 demonstrate that 2-D hydraulic modeling allowed a much better match between the spatial scale of salmonid function and hydraulic predictions. Crowder and Diplas [2000] showed that point measurements of habitat did not represent habitat variation in space by using a model that included mesoscale topographic features (e.g., boulders).…”
Section: Introductionmentioning
confidence: 99%
“…For sea lamprey larval habitat, n= 1, which represents substrate. Depending on the value of exponent p, expression (2) corresponds to either the Interactive Limiting Factor (ILF) method ( p=1) or the Average Value Method (AVM) ( p = 1/n) (Minns and Bakelaar 1999;Leclerc et al 1996). Both methods assume that the overall HSI for a reach j is a function of the product of the characteristics.…”
Section: Resultsmentioning
confidence: 99%